Application of a 3D Bioprinted Hepatocellular Carcinoma Cell Model in Antitumor Drug Research - Sun, Lejia; Yang, Huayu; Wang, Yanan; Zhang, Xinyu; Jin, Bao; Xie, Feihu; Jin, Yukai; Pang, Yuan; Zhao, Haitao; Lu, Xin; Sang, Xinting; Zhang, Hongbing; et al. (Frontiers in Oncology, 2020)
The existing in vitro model for anti-tumor drug screening has great limitations. Many compounds that inhibit 2D cultured cells do not exhibit the same pharmacological effects in vivo, resulting a waste of human and material resources as well as time waste during drug development. Therefore, developing new models is critical. The 3D bioprinting technology has greater advantages in constructing human tissue than sandwich culture and organoid construction. Here we used 3D bioprinting technology to construct a 3D model with HepG2 cells (3DP-HepG2). The biological activities of the model were evaluated by immunofluorescence, real-time quantitative PCR and transcriptome sequencing. Compared with traditional 2D cultured tumor cells (2D-HepG2), the 3DP-HepG2 model showed significantly improved expression of tumor-related genes, including ALB, AFP, CD133, IL-8, EpCAM, CD24 and β-TGF genes. Transcriptome sequencing analysis revealed large differences in gene expressions between 3DP-HepG2 and 2D-HepG2 models, especially genes related to hepatocyte function and tumor. We also compared the effects of anti-tumor drugs in the 3DP-HepG2 and 2D-HepG2 models and found that the large differences in drug resistance genes between the models may be one reason for the difference in pharmacodynamics.